A triple blind, randomised, placebo controlled, add-on trial to assess the efficacy and safety of dexmedetomidine in facilitation of general anaesthesia in patients undergoing elective spine surgery - Ray, Madhumita; Dalai, Chanchal Kumar; Ahmed, Shah Newaz; Acharjee, Amita (Asian Journal of Medical Sciences, 2021)
Background: Dexmedetomidine is a centrally acting sympatholytic drug acting as an agonist on alpha2 receptors. Of late, the drug has become popular in anaesthesia because of its sedative, analgesic and anti-adrenergic effects. Aims and Objectives: We conducted a single centre, randomised, placebo controlled, triple blinded add-on trial to assess the efficacy and safety of the drug as an adjuvant in general anaesthesia (GA) during elective spine surgery. Materials and Methods: Anaesthesia was induced and maintained using standard method in all the patients (N=60). Concomitantly, patients in the treatment arm (n=30) and control arm (n=30) were infused with dexmedetomidine and normal saline respectively. The anaesthetic sparing effect, hemodynamic stability, and adverse events of dexmedetomidine were assessed using pre-defined outcome parameters. Results: Anaesthetic Sparing Effect: Dexmedetomidine produced statistically significant reduction in the requirement of propofol and fentanyl during GA (p<0.001). There was no significant difference in requirement of rocuronium (p=0.25). Hemodynamic Stability: The cardiovascular stimulation during surgery, in general, and during stress of artificial endotracheal access, in particular, were attenuated in the treatment arm. The heart rate (HR) and mean arterial pressure (MAP), in the control and treatment arm became greater and lesser than the baseline value respectively, at all the time points following induction. The HR and MAP remained close to baseline values during intubation and extubation in the treatment arm but surged significantly in the control arm (p<0.001). Adverse Events: The number of episodes of hypotension, hypertension and bradycardia in the control arm was 1, 18 and 1 respectively. In the treatment arm, 2 episode each of hypotension and bradycardia and none of hypertension occurred. Conclusion: Dexmedetomidine, which is being increasingly used as an adjuvant in GA in various types of surgeries, also plays an auxiliary role in facilitation of GA in spine surgery. It decreases requirement of the primary anaesthetic agents, and also mitigates intra-operative cardiovascular instability without causing any significant adverse effect.